The Influence of ROA, BOPO, CAR, and FDR on Non-Performing Financing in Full-Fledged Islamic Banks - Elva Octavia Sari; Fatmi Hadiani; Hazma Hazma (Indonesian Journal of Economics and Management, 2022)
Islamic banks have the main activity of distributing funds in the form of financing. Therefore, banks cannot be separated from financing risks. The financing risk is non-performing financing. Non-Performing Financing is a ratio that shows the large collectability of the bank in collecting back the financing. This study aims to determine the effect of CAR, ROA, FDR, and BOPO on NPF in Islamic Commercial Banks for the 2015-2020 period. This research is quantitative research and uses the panel data regression method. The data used are sourced from the financial statements of each Islamic Commercial Bank. The results showed that simultaneously the variables CAR, ROA, FDR, and BOPO have a significant positive effect on NPF. Partially, the CAR and BOPO variables have no significant effect on the NPF while the ROA variable has a significant negative effect on the NPF and FDR has a significant positive effect on the NPF.